TINJAUAN TINGKAT KEAKURATAN KODE DIAGNOSIS TYPHOID FEVER PASIEN RAWAT INAP BERDASARKAN ICD 10 DI PUSKESMAS GULUK-GULUK - Ayu Soviana; M. Afif Rijal Husni (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
The diagnosis code is said to be accurate if it is following what is written in the ICD-10. The determination of the diagnosis code for Typhoid Fever at Puskesmas Guluk-Guluk uses a smart book and the code is not specified with the fourth character. The purpose of this study is to review the accuracy of the Typhoid Fever diagnosis code for inpatients based on ICD-10 at Puskesmas Guluk-Guluk. The type of research used was descriptive quantitative research with a retrospective approach. The population of this study was medical record files of inpatients with a diagnosis of Typhoid Fever. The sampling technique used was random sampling. The results of the study from a total sample of 51 files of inpatient medical records for Typhoid Fever patients at Puskesmas Guluk-Guluk obtained 18 medical record files with accurate diagnosis codes (35.3%) and 33 medical record files with inaccurate diagnosis codes (64.7%). The results can be concluded that the inaccuracy is due to the diagnosis code not being obtained from the ICD-10  but from the smart book and not specified with the fourth character. It is recommended that coding officers in the coding process use ICD-10 to ensure the accuracy of the diagnosis code.